Flood affectedness and household adaptation measures in rural northern Chile: a cross-sectional study in the Upper Huasco Valley - Meltzer, Laura; Dame, Juliane; Gabrysch, Sabine (International journal of disaster risk reduction, 2021)
Climate change is increasing the frequency and intensity of extreme events. Adaptation strategies at societal and household level are crucial to reduce vulnerability. We assessed to what extent personal flood affectedness, in particular health impacts, influence adaptive behavior. We conducted a cross-sectional survey in northern Chile one year after a major flood event and assessed several dimensions of flood affectedness and adaptive behavior at the household level. After the event, a wide range of adaptation measures, including water storage and preparation of emergency kits, had been implemented by 80% of the population.